SISTEM KONTROL KONVEYOR PEMILAH LOGAM MENGGUNAKAN PLC OMRON CP1E - Alimuddin Mappa; Sonny Rumalutur; Marco Mambrisaw (LPPM Poltek ST Paul, 2020)
The research conducted aims to create an automatic metal sorting control system using the PLC Omron CP1E30 with a ladder diagram program designed with the CX-Programmer application.The PLC input used contains one proximity sensor and two photoelectric sensors, while the output includes two conveyor motors and a solenoid.The proximity sensor functions to detect metal and non-metal objects and the photoelectric sensor functions to detect the presence of an object passing through it. PLC output contains two conveyor motors that carry objects to be separated and selenoid which functions to separate metal and non-metal objects.Based on the test results it turns out that the system can function properly where when the PLC is activated, the conveyor motor 1 will be active to carry the object to be sorted, when the object passes the photoelectric sensor 1, the conveyor motor 1 will stop to be detected by the proximity sensor, if the object is non-metal, the conveyor motor 2 will carry the non-metal object to the end of the conveyor 2, after the non-metal object is detected by photoelectric sensor 2, the conveyor motor 1 activates again to deliver the next object. If the proximity sensor detects that the object is metal, the selenoid is activated so that it separates the metal object.